Degradable hydrophobic polyurethane as well as preparation method and application thereof

By using raw materials such as polycaprolactone, polylactic acid and terminal hydroxyl polydimethylsiloxane, the degradable hydrophobic polyurethane is solved, and the application of existing polyurethane materials in the field of marine anti-fouling is combined, and the combination of high mechanical properties, good hydrophobic properties and excellent degradation properties is achieved. It is suitable for the surface anti-fouling of marine materials.

CN119859241AActive Publication Date: 2025-04-22SHANDONG HAIHUA GRP CO LTD

Patent Information

Application Number
CN202510358258.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

Existing polyurethane materials are limited in the field of marine anti-fouling due to their poor non-degradable and anti-adhesion properties.

Method used

Degradable hydrophobic polyurethane with soft and hard segments were prepared by using raw materials such as polycaprolactone, polylactic acid and terminal hydroxy polydimethylsiloxane through N,N-dimethylformamide dissolution and isophorone diisocyanate catalytic reaction.

Benefits of technology

It improves the mechanical properties, hydrophobic properties and degradation properties of polyurethane. It has tensile strength exceeds 40MPa, elongation rate of break exceeds 400%, water contact angle exceeds 130°, and the degradation rate reaches more than 99% under specific conditions, and has good anti-fouling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859241A_ABST
    Figure CN119859241A_ABST
Patent Text Reader

Abstract

The invention provides degradable hydrophobic polyurethane as well as a preparation method and application thereof, and relates to the technical field of polyurethane synthesis and modification. The preparation method comprises the following steps: adding polycaprolactone, polylactic acid and hydroxyl-terminated polydimethylsiloxane into N, N-dimethylformamide to obtain a mixed solution, then adding isophorone diisocyanate and an organic metal catalyst, and carrying out a catalytic reaction to prepare a prepolymer solution; and adding a polyol chain extender, a polyol cross-linking agent and a non-aqueous polyurethane defoaming agent into the prepolymer solution, uniformly stirring to obtain a polyurethane emulsion, and carrying out vacuum degassing and curing on the polyurethane emulsion to obtain the degradable hydrophobic polyurethane. The prepared polyurethane has excellent mechanical properties, degradability and antifouling property, and is applied to surface antifouling of marine materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane preparation, and particularly relates to a degradable hydrophobic polyurethane and a preparation method and application thereof. Background Art

[0002] Marine industry and marine activities inevitably encounter the problem of marine fouling organisms attaching and contaminating, which has brought huge negative impacts to marine engineering projects such as ships, nuclear power plants, and oil platforms. It is difficult for people to control the natural environment in which ships or marine facilities are located. Therefore, changing the surface characteristics of marine facilities by applying marine antifouling coatings to resist the adhesion of fouling organisms has become the most economical and feasible method. Acrylic self-polishing antifouling coatings are currently the most widely used materials, but the mechanical properties of acrylic resins are poor. Polyurethane is a type of material synthesized from raw materials such as polyols, isocyanates, and chain extenders. Ordinary polyurethane has good mechanical properties, but it is non-degradable and has poor anti-adhesion properties, which makes it difficult to apply to the field of marine antifouling; therefore, it is modified to change its properties so that the polyurethane obtains degradable properties, which can greatly improve the antifouling properties of polyurethane and better apply it to the field of marine materials.

[0003] A Chinese patent document with publication number CN112409776A discloses a method for preparing rapidly degradable polyurethane, which is synthesized using polyurethane particles, urea-formaldehyde resin, plant starch, polyurethane prepolymer, dioctyl phthalate, polyvinyl butyral, a photodegradation agent, a photosensitizer and a catalyst, wherein the front-end polyol of the degradable unit is a block polymer of an aliphatic polyester and polyoxyethylene ether; the mechanical properties of the prepared polyurethane are average (tensile strength is 26.18-32.65MPa, elongation at break is 309.5-352.5%), and its degradation conditions are relatively harsh, and the degradation rate can only reach 97.63-99.85 under alkaline conditions.

[0004] A Chinese patent document with publication number CN118184954A discloses a degradable material with added starch. It uses toluene diisocyanate and polytetramethylene glycol as base materials. By modifying and compounding the straight-chain starch into the polymer material, a degradable polyurethane is obtained. However, its mechanical properties are poor, with a tensile strength of only 4.27-5.13 MPa and an elongation at break of 161-205%. The degradation rate after 120 days is 91.52-94.51%, which makes it difficult to apply in actual scenarios. Summary of the invention

[0005] The purpose of the present invention is to provide a degradable hydrophobic polyurethane which is easily degradable and has strong mechanical properties and a preparation method thereof. The material is suitable for surface antifouling of marine materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a degradable hydrophobic polyurethane, the general structural formula of the degradable hydrophobic polyurethane is as follows:

[0007] Among them, 1.2≤m≤31, 1≤n≤20, 1≤y≤26.

[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned degradable hydrophobic polyurethane, comprising the following steps: (1) adding polycaprolactone, polylactic acid and terminal hydroxyl polydimethylsiloxane to N,N-dimethylformamide, stirring and dissolving to obtain a mixed solution, adding isophorone diisocyanate to the mixed solution, stirring evenly, and then adding an organic metal catalyst to catalyze a reaction to obtain a prepolymer solution; (2) Adding a polyol chain extender, a polyol cross-linking agent, and a non-aqueous polyurethane defoaming agent to the prepolymer solution, stirring the mixture evenly to obtain a polyurethane emulsion, and vacuum degassing and curing the polyurethane emulsion to obtain a degradable hydrophobic polyurethane.

[0009] Furthermore, in the step (1), the mass ratio of the terminal hydroxyl polydimethylsiloxane, polycaprolactone and polylactic acid is 1:1.5-2:1.2-1.5; and the amount of isophorone diisocyanate used is 20-50% of the total mass of the terminal hydroxyl polydimethylsiloxane, polycaprolactone and polylactic acid.

[0010] Furthermore, in the step (1), the amount of isophorone diisocyanate used is 30% of the total mass of the hydroxy-terminated polydimethylsiloxane, polycaprolactone and polylactic acid.

[0011] Furthermore, in step (1), the organic metal catalyst is dibutyltin dilaurate or stannous octoate, and its amount is 0.1-1% of the mass of isophorone diisocyanate.

[0012] Furthermore, in the step (1), the catalytic reaction temperature is controlled at 50-90°C; and the catalytic reaction time is controlled at 2-4h.

[0013] Furthermore, in step (2), the polyol chain extender is any one of 1,4-butanediol, propylene glycol, dimethylbenzene glycol, and triethanolamine, and its usage is 10-15% of the mass of isophorone diisocyanate; the polyol cross-linking agent is any one of trimethylolpropane, pentaerythritol, and trihydroxymethylethane; the non-aqueous polyurethane defoamer is any one of YRXP-02, YRXP-07, and YRXP-07B; and the mass ratio of the polyol chain extender to the polyol cross-linking agent to the non-aqueous polyurethane defoamer is 1:0.4-0.6:0.03-0.05.

[0014] In a third aspect, the present invention provides an application of a degradable hydrophobic polyurethane material prepared by the above preparation method, wherein the above material is applied to the surface antifouling of marine materials.

[0015] Compared with the prior art, the technical solution of the present invention has the following beneficial effects.

[0016] The degradable hydrophobic polyurethane material provided by the invention comprises a soft segment and a hard segment. The soft segment comprises hydroxyl-terminated polydimethylsiloxane, polycaprolactone and polylactic acid segments, and the hard segment comprises isophorone diisocyanate. Since the polylactic acid segments have high crystallinity and high ester bond content, and the isophorone diisocyanate provides a large number of isocyanate groups, the hardness of the material is improved and the tensile strength of the material is enhanced. The hydroxyl-terminated polydimethylsiloxane contains a large number of silicon-oxygen bonds and has a weak intermolecular force, so that the segments can have a certain fluidity. The molecular chain of polycaprolactone contains aliphatic segments with relatively large flexibility. These segments are composed of carbon atoms, have relatively large flexibility, and can freely move the segments. Therefore, the hydroxyl-terminated polydimethylsiloxane and the polycaprolactone segments mainly provide good flexibility for the material and enhance the elongation at break of the material.

[0017] Polylactic acid and polycaprolactone chain segments contain a large number of hydrolyzable ester bonds, which are easily hydrolyzed and broken in the presence of water and microorganisms, giving the polyurethane material excellent degradation properties.

[0018] The terminal hydroxyl polydimethylsiloxane provides a large number of siloxy bonds, and the polycaprolactone segment provides a large number of long-chain alkyl groups and ester bonds. These groups are hydrophobic groups with excellent performance. Their synergistic effect together makes the polyurethane material have excellent hydrophobic properties.

[0019] The preparation method disclosed by the invention adopts polycaprolactone, polylactic acid, terminal hydroxyl polydimethylsiloxane and isophorone diisocyanate as raw materials to prepare a degradable hydrophobic polyurethane material. Compared with the prior art, the preparation process is simple, the manufacturing cost is low, and the material is suitable for large-scale industrial production. The prepared polyurethane material has excellent mechanical properties, hydrophobic properties and degradation properties, and its tensile strength exceeds 40MPa, its elongation at break exceeds 400%, and its water contact angle exceeds 130°; the material degradation rate exceeds 99% in 120 days under the conditions of 58°C and 50° humidity, and the material degradation rate exceeds 30% in 120 days under the conditions of 25°C seawater; in a scraper test, the material still has good antifouling performance after 600 days, which meets the practicality; and compared with the existing antifouling coating, the polyurethane raw material prepared by the invention is green and environmentally friendly, and is suitable for surface antifouling of marine materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the infrared spectrum of the degradable polyurethane material obtained in Example 1; in the figure, Transmittance represents infrared transmittance, and Wavenumber represents the infrared spectrum wavenumber. DETAILED DESCRIPTION

[0021] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods adopted in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels. Through these descriptions, the characteristics and advantages of the present invention will become clearer and more specific. Example 1

[0022] Weigh 76 g of hydroxy-terminated polydimethylsiloxane, 114 g of polycaprolactone and 91.2 g of polylactic acid and place them in a vacuum oven for drying for 1 h, then add them to a three-necked flask and add 100 mL of N,N-dimethylformamide and stir until completely dissolved to obtain a mixed solution, add 84.36 g of isophorone diisocyanate to the mixed solution, raise the temperature to 85 ° C while stirring, and add 0.8436 g of catalyst stannous octoate at the same time. After reacting for 2 h, a prepolymer solution is obtained. liquid; 8.436g of chain extender 1,4-butanediol (BDO), 3.3744g of cross-linker trimethylolpropane (TMP) and 0.253g of defoamer YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60°C, then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1MPa to remove bubbles, and cured at room temperature for 3d to obtain a degradable hydrophobic polyurethane, recorded as PDMS-PCL 1.5 -PLA 1.2 -PU.

[0023] Figure 1 For PDMS-PCL1.5 -PLA 1.2 -Infrared spectrum of PU material. It can be seen from the figure that 3383cm -1 The mixed peak attributable to stretching vibration of amide and hydroxyl groups; 2954 cm -1 The stretching vibration peak of methyl-CH3 in the chain segment is 2838cm -1 The peak of methylene-CH2 stretching vibration in the chain segment is 1750cm -1 The absorption peak is attributed to the carbonyl C=O stretching vibration in the amide; 1513cm -1 The absorption peak is attributed to the NH deformation vibration in the urea group; 1139cm -1 Belongs to Si-O in the chain segment; 1082cm -1 Belongs to the Si-C peak, 936 cm -1 The peak is attributed to the out-of-plane bending vibration of the CH ring in the chain segment, which should be located at 2200-2280cm -1 The representative N=C=O stretching vibration peak in the wave number range disappears, from which it can be judged that the polyurethane segment synthesized by this method contains terminal hydroxyl polydimethylsiloxane, polylactic acid and polycaprolactone segments at the same time, proving its successful synthesis. Based on this, its general structural formula is analyzed as follows: Example 2

[0024] Weigh 740g of terminal hydroxyl polydimethylsiloxane, 1295g of polycaprolactone and 962g of polylactic acid, and put them into a vacuum oven for drying for 1h, then add them into a three-necked flask and add 1000mL of N,N-dimethylformamide and stir at room temperature until completely dissolved, then add 1215g of isophorone diisocyanate, raise the temperature to 85°C while stirring, and add 1.2g of catalyst stannous octoate at the same time. After reacting for 4h, stop the reaction to obtain a prepolymer solution; add 182.2g of chain extender propylene glycol, 109.32g of cross-linking agent trimethylolpropane (TMP) and 9.11g of defoamer YRXP-07 (produced by Guangzhou Yourun New Materials Co., Ltd.) to the prepolymer solution, stir evenly at 60°C, then pour into a polytetrafluoroethylene mold, put it into a vacuum oven at -0.1MPa to remove bubbles, and cure it at room temperature for 3d to obtain a degradable hydrophobic polyurethane PDMS-PCL. 1.75 -PLA 1.3 -PU; its structural formula is: Example 3

[0025] Weigh 1482g of hydroxy-terminated polydimethylsiloxane, 2964g of polycaprolactone and 1926.6g of polylactic acid and put them into a vacuum oven for drying for 1h, then add them into a three-necked flask and add 2000mL of N,N-dimethylformamide and stir at room temperature until completely dissolved, then add 1911.78g of isophorone diisocyanate, raise the temperature to 85°C while stirring, and add 11.86g of catalyst stannous octoate at the same time, and stop the reaction after reacting for 3h to obtain a prepolymer. solution; add 237.12g of chain extender dimethylene phenyl glycol, 132.7872g of cross-linker trihydroxymethylethane and 11.1446g of defoamer YRXP-07 (produced by Guangzhou Yourun New Materials Co., Ltd.) to the prepolymer solution, stir evenly at 60°C, then pour into a polytetrafluoroethylene mold, put it in a vacuum oven at -0.1MPa to remove bubbles, and cure it at room temperature for 3d to obtain a degradable hydrophobic polyurethane PDMS-PCL2-PLA. 1.3 -PU; its structural formula is: Example 4

[0026] Weigh 1485g of hydroxy-terminated polydimethylsiloxane, 2598.75g of polycaprolactone and 2227.5g of polylactic acid and place them in a vacuum oven for drying for 1h, then add them to a three-necked flask and add 2000mL of N,N-dimethylformamide and stir at room temperature until completely dissolved, then add 1893.375g of isophorone diisocyanate, raise the temperature to 85°C while stirring, and add 11.9283g of catalyst stannous octoate at the same time. After reacting for 3h, stop the reaction. A prepolymer solution should be obtained; 227.205 g of chain extender 1,4-butanediol, 127.2348 g of cross-linker trihydroxymethylethane and 9.0882 g of defoamer YRXP-07 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60°C, then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL. 1.75 -PLA 1.5 -PU; its structural formula is: Example 5

[0027] Weigh 1480 g of hydroxy-terminated polydimethylsiloxane, 2960 g of polycaprolactone and 2220 g of polylactic acid, put them into a vacuum oven for drying for 1 h, then add them into a three-necked flask and add 2000 mL of N,N-dimethylformamide and stir at room temperature until completely dissolved, then add 1998 g of isophorone diisocyanate, raise the temperature to 85 ° C while stirring, and add 14.7852 g of catalyst stannous octoate at the same time. After reacting for 3 h, stop the reaction to obtain a prepolymer 299.7 g of chain extender 1,4-butanediol, 149.85 g of cross-linker trimethylolpropane and 13.4865 g of defoamer YRXP-07B (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL2-PLA. 1.5 -PU; its structural formula is: Example 6

[0028] 740 g of hydroxy-terminated polydimethylsiloxane, 1110 g of polycaprolactone and 888 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 1000 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 547.6 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 5.476 g of catalyst stannous octoate was added at the same time. After reacting for 3 h, a prepolymer solution was obtained; 82.14 g of chain extender 1, 4-butanediol (BDO), 32.856 g of cross-linking agent trimethylolpropane (TMP) and 2.4642 g of defoamer YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane, recorded as PDMS-PCL 1.5 -PLA 1.2 -PU1; its structural formula is: Example 7

[0029] 100 g of hydroxy-terminated polydimethylsiloxane, 150 g of polycaprolactone and 120 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 185 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 1.48 g of catalyst stannous octoate was added at the same time. After reacting for 4 h, a prepolymer solution was obtained; 20.35 g of chain extender 1, 4-butanediol (BDO), 12.21 g of cross-linking agent trimethylolpropane (TMP) and 0.814 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane, recorded as PDMS-PCL 1.5 -PLA 1.2 -PU2; its structural formula is: Comparative Example 1

[0030] 150 g of polycaprolactone and 150 g of polylactic acid were weighed and placed in a vacuum oven for drying for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 90 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 0.504 g of catalyst stannous octoate was added at the same time. After the prepolymerization reaction for 3 h, the reaction was stopped to obtain a prepolymer; 10.8 g of chain extender 1, 4-butanediol (BDO), 6.156 g of cross-linking agent trimethylolpropane (TMP) and 0.5184 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PCL-PLA-PU. Comparative Example 2

[0031] 100 g of hydroxy-terminated polydimethylsiloxane and 150 g of polylactic acid were weighed and placed in a vacuum oven for drying for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 75 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 0.5025 g of catalyst stannous octoate was added at the same time. After 3 h of prepolymerization, the reaction was stopped to obtain a prepolymer; 10.5 g of chain extender 1, 4-butanediol (BDO), 5.985 g of cross-linking agent trimethylolpropane (TMP) and 0.504 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PLA. 1.5 -PU. Comparative Example 3

[0032] 100 g of hydroxy-terminated polydimethylsiloxane and 150 g of polycaprolactone were weighed and placed in a vacuum oven for drying for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 75 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 0.5025 g of catalyst stannous octoate was added at the same time. After 3 h of prepolymerization, the reaction was stopped to obtain a prepolymer; 10.5 g of chain extender 1, 4-butanediol (BDO), 5.985 g of cross-linking agent trimethylolpropane (TMP) and 0.504 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL. 1.5 -PU. Comparative Example 4

[0033] 200 g of hydroxy-terminated polydimethylsiloxane, 150 g of polycaprolactone and 120 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 141 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 1.41 g of catalyst stannous octoate was added at the same time. After reacting for 2 h, the reaction was stopped to obtain a prepolymer solution; 15.51 g of chain extender 1, 4-butanediol, 7.755 g of cross-linking agent trihydroxymethylethane and 0.6049 g of defoaming agent YRXP-07 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL-PLA-PU. Comparative Example 5

[0034] Weigh 100 g of hydroxy-terminated polydimethylsiloxane, 300 g of polycaprolactone and 120 g of polylactic acid, put them into a vacuum oven for drying for 1 h, then add them into a three-necked flask and add 100 mL of N, N-dimethylformamide and stir at room temperature until completely dissolved, then add 156 g of isophorone diisocyanate, heat to 85 ° C while stirring, and add 1.56 g of catalyst stannous octoate. After reacting for 2 h, stop the reaction to obtain a prepolymer solution; add 23.4 g of chain extender 1, 4-butanediol, 11.7 g of cross-linking agent trihydroxymethylethane and 1.17 g of defoaming agent YRXP-07 (produced by Guangzhou Yourun New Materials Co., Ltd.) to the prepolymer solution, stir evenly at 60 ° C, then pour into a polytetrafluoroethylene mold, put it into a vacuum oven under -0.1 MPa to remove bubbles, and cure at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL3-PLA. 1.5 -PU. Comparative Example 6

[0035] 100 g of hydroxy-terminated polydimethylsiloxane, 150 g of polycaprolactone and 200 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 135 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 1.35 g of catalyst stannous octoate was added at the same time. After reacting for 2 h, the reaction was stopped to obtain a prepolymer solution; 19.98 g of chain extender 1, 4-butanediol, 11.988 g of cross-linking agent trihydroxymethylethane and 0.999 g of defoaming agent YRXP-07B (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL2-PLA2-PU. Comparative Example 7

[0036] 100 g of hydroxy-terminated polydimethylsiloxane, 150 g of polycaprolactone and 120 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 37 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 1.11 g of catalyst stannous octoate was added at the same time. After reacting for 2 h, the reaction was stopped to obtain a prepolymer solution; 11.1 g of chain extender 1, 4-butanediol (BDO), 4.44 g of cross-linking agent trimethylolpropane (TMP) and 0.333 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL. 1.5 -PLA 1.2 -PU-1. Comparative Example 8

[0037] 100 g of hydroxy-terminated polydimethylsiloxane, 150 g of polycaprolactone and 120 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 240.5 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 1.1063 g of catalyst stannous octoate was added at the same time. After reacting for 2 h, the reaction was stopped to obtain a prepolymer solution; 11.063 g of chain extender 1, 4-butanediol (BDO), 4.4252 g of cross-linking agent trimethylolpropane (TMP) and 0.3319 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL. 1.5 -PLA 1.2 -PU-2. Comparative Example 9

[0038] Weigh 100 g of terminal hydroxyl polydimethylsiloxane, 150 g of polycaprolactone and 120 g of polylactic acid and put them into a vacuum oven for drying for 1 hour. Then add them into a three-necked flask and add 100 mL of N,N-dimethylformamide and stir at room temperature until completely dissolved. Then add 1.11 g of catalyst stannous octoate and then 111 g of isophorone diisocyanate. Then, explosion occurs, generating a large amount of foaming and yellowing, making it impossible to carry out subsequent experiments. Comparative Example 10

[0039] 100 g of hydroxy-terminated polydimethylsiloxane, 150 g of polycaprolactone and 120 g of polylactic acid were weighed and dried in a vacuum oven for 1 h, then added to a three-necked flask and 100 mL of N, N-dimethylformamide was added and stirred at room temperature until completely dissolved, 111 g of isophorone diisocyanate was added, the temperature was raised to 85 ° C while stirring, and 1.11 g of catalyst stannous octoate was added at the same time. After reacting for 2 h, the reaction was stopped to obtain a prepolymer solution; 29.97 g of chain extender 1, 4-butanediol (BDO), 20.0799 g of cross-linking agent trimethylolpropane (TMP) and 2.997 g of defoaming agent YRXP-02 (produced by Guangzhou Yourun New Materials Co., Ltd.) were added to the prepolymer solution, stirred evenly at 60 ° C, and then poured into a polytetrafluoroethylene mold, placed in a vacuum oven at -0.1 MPa to remove bubbles, and cured at room temperature for 3 days to obtain a degradable hydrophobic polyurethane PDMS-PCL. 1.5 -PLA 1.2 -PU-3. Comparative Example 11

[0040] The degradable polyurethane is prepared according to the method described in Chinese patent document CN112409776A. Comparative Example 12

[0041] The degradable polyurethane is prepared according to the method described in Chinese patent document CN118184954A.

[0042] In order to verify the technical effect of the present invention, the polyurethane films prepared in the embodiments and comparative examples were tested for mechanical properties, water contact angle and degradability, respectively. The mechanical properties were tested using a universal tensile machine in accordance with GB / T1040-92, and the results are shown in Table 1; the water contact angle was tested using a water contact angle measuring instrument in accordance with GB / T30693, and the experimental results are shown in Table 1; the degradability test was carried out using a controlled composting degradation device and a controlled seawater degradation device, and the implementation standards were GB / T19277 and ISO19679, respectively. The environmental conditions for controlled composting degradation were set to 58°C and 50% humidity, and the temperature for seawater degradation was 25°C. The polyurethane samples in the embodiments and comparative examples were cultured in different environments, and the degradation degrees of the polyurethane samples were recorded. The experimental results are shown in Table 2.

[0043]

[0044] As can be seen from Table 1, the tensile strength and elongation at break of the polyurethane materials obtained using Examples 1-7 are 40.11-48.19 MPa and 402-482%, respectively. Compared with Comparative Examples 1-3, the tensile strength, elongation at break and hydrophobicity of Examples 1-7 are significantly enhanced, which indicates that the performance of the three-component polyurethane prepared using polydimethylsiloxane, polycaprolactone and polylactic acid is significantly better than that of the two-component polyurethane. Furthermore, as can be seen from Comparative Examples 1-3, the terminal hydroxyl polydimethylsiloxane mainly provides siloxane bonds, thereby increasing the flexibility and hydrophobicity of the material, while polylactic acid and polycaprolactone contain a large number of ester bonds, which can increase the tensile strength of the material, and the long-chain alkyl groups in polycaprolactone can also form a synergistic effect with the siloxane bonds to enhance the hydrophobicity of the material.

[0045] Compared with Example 1, the tensile strength and elongation at break of Comparative Example 4 are significantly reduced, while the hydrophobic properties are basically the same, which indicates that as the amount of polydimethylsiloxane exceeds 1:1.5-2:1.2-1.5, the silicon oxygen content increases, the intermolecular force between the chain segments is weakened, and the mechanical properties of the material are reduced; and in Comparative Example 5, it can be seen that as the amount of polycaprolactone exceeds 1:1.5-2:1.2-1.5, the alkyl chains in the material grow, the crosslinking ratio between the long alkyl chains decreases, and the material The mechanical properties of the material are reduced, and the increase in the alkyl chain content reduces the synergistic effect of the alkyl chain and the siloxane bond, thereby reducing the hydrophobicity of the material; in Comparative Example 6, as the polylactic acid usage ratio exceeds 1:1.5-2:1.2-1.5, the content of short-chain polylactic acid segments in the polyurethane increases, which increases the crystallinity of the molecular chain, resulting in poor flexibility of the molecular chain, which significantly reduces its elongation at break. In addition, the increase in the polylactic acid content increases the ester bond content in the segment, which is easier to form hydrogen bonds with water, thereby reducing the hydrophobicity of the material.

[0046] Compared with Example 1, it can be seen from Comparative Examples 7 and 8 that since the isocyanate segment is a hard segment in the polyurethane, its amount exceeding 1:0.2-0.5 will significantly affect the mechanical properties of the material, and its amount exceeding 1:0.5 will make the material too hard and the elongation at break will be significantly reduced, and its amount below 1:0.2 and too low a content will result in insufficient tensile strength of the material.

[0047] Compared with Example 1, it can be seen from Comparative Example 10 that when the ratio of isophorone diisocyanate to chain extender exceeds 1:0.1-0.15, the flexibility of the material will also deteriorate and the elongation at break will decrease.

[0048] Compared with comparative examples 11 and 12 of the prior art, the material prepared by the present invention is significantly superior to other existing patents in terms of mechanical properties and hydrophobic properties.

[0049]

[0050] As can be seen from Table 2, in Examples 1-5 obtained by the preparation method of the present invention, under the conditions of biological composting, the 120-day degradation performance of Examples 1-5 and Comparative Examples 5 and 6 is relatively excellent, reaching more than 99%. Similarly, the degradation effect under the conditions of simulated seawater degradation that is difficult to degrade is also more than 30%, which shows that the degradation performance of the material is mainly affected by the polycaprolactone and polylactic acid segments in the material. However, when the content of polycaprolactone and polylactic acid segments exceeds 1:1.5-2:1.2-1.5, the degradation performance of the material will not continue to increase.

[0051] Compared with Example 1, the 120-day degradation rate in Comparative Example 4 is significantly reduced. This is because the amount of terminal hydroxyl polydimethylsiloxane exceeds 1:1.5-2:1.2-1.5, which significantly reduces the proportion of ester bonds in the chain segment and reduces the hydrolysis performance.

[0052] Moreover, compared with comparative examples 11 and 12, the materials prepared in Examples 1-5 have excellent degradation performance, indicating that compared with the existing patents, the degradable hydrophobic polyurethane material prepared in the present invention also has obvious degradation effect, and the preparation method is simple, the process equipment requirements are low, and it can be widely used in the field of environmental protection, and has extremely strong use value and promotion and application prospects. Application Examples

[0053] Taking into account the mechanical properties, water contact angle and degradation effect, the material prepared in Example 5 was selected as an application example, and a 40cm*40cm*4.5cm low-carbon steel plate was selected as the base layer. After sandblasting, cleaning and drying, a layer of Henri Pioneer Shield epoxy zinc-rich primer 750 was brushed on its surface. After drying, the polyurethane film prepared in Example 1 was bonded to the base with epoxy zinc-rich primer 750. After curing for 24 hours, a polyurethane-modified base composite material was obtained. The above-prepared composite material was placed in seawater. After 120 days, the composite base was taken out for comparison with the attachment of marine organisms on the original base. The results are shown in Table 3. Application Comparative Example 1

[0054] The seawater scraper experiment was carried out with the original low-carbon steel plate as the substrate. It was placed in seawater. After 120 days, the composite substrate was taken out and compared with the marine organism attachment on the original substrate. The results are shown in Table 3. Application Comparative Example 2

[0055] The material prepared in Comparative Example 11 was selected as Application Comparative Example 2, and a 40cm*40cm*4.5cm low-carbon steel plate was selected as the base layer. After sandblasting, cleaning and drying, a layer of Henri Pioneer Shield epoxy zinc-rich primer 750 was brushed on the surface. After drying, the polyurethane film prepared in Comparative Example 11 was coated on the epoxy zinc-rich primer 750. After curing for 24 hours, a polyurethane-modified base composite material was obtained. The above-prepared composite material was placed in seawater. After 120 days, the composite base was taken out for comparison with the attachment of marine organisms on the original base. The results are shown in Table 3. Application Comparative Example 3

[0056] The material prepared in Comparative Example 12 was selected as Application Comparative Example 3, and a 40cm*40cm*4.5cm low-carbon steel plate was selected as the base layer. After sandblasting, cleaning and drying, a layer of Henri Pioneer Shield epoxy zinc-rich primer 750 was brushed on the surface. After drying, the polyurethane film prepared in Comparative Example 12 was coated on the epoxy zinc-rich primer 750. After curing for 24 hours, a polyurethane-modified base composite material was obtained. The above-prepared composite material was placed in seawater. After 120 days, the composite base was taken out for comparison with the attachment of marine organisms on the original base. The results are shown in Table 3.

[0057]

[0058] As can be seen from Table 3, after the material was subjected to the hanging board test, after 120 days of natural seawater and biological corrosion, the mass of the original steel plate and the different modified steel plates increased. The increased mass is the mass increased after the marine biological fouling and attachment. Compared with the original steel plate, the modified steel plates all achieved a certain anti-fouling effect, and the most obvious effect was the application example, with a mass increase rate of less than 10% in 120 days, which was significantly better than application examples 2 and 3. In order to verify the service life of the material, the application example continued to be subjected to the hanging board test until 600 days, and compared with the original substrate of application example 1, the experimental data are shown in Table 4, indicating that the material obtained by this method has excellent practical application effect.

[0059]

[0060] The present invention is described in detail above in combination with preferred embodiments and normative examples. However, it should be noted that these specific embodiments are illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications can be made to the technical content of the present invention and its implementation methods, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A degradable hydrophobic polyurethane, characterized in that: The general structural formula of the degradable hydrophobic polyurethane is as follows: , Among them, 1.2≤m≤31, 1≤n≤20, 1≤y≤26.

2. A method for preparing the degradable hydrophobic polyurethane according to claim 1, characterized in that: The steps include: (1) adding polycaprolactone, polylactic acid and terminal hydroxyl polydimethylsiloxane into N,N-dimethylformamide to dissolve to obtain a mixed solution, adding isophorone diisocyanate to the mixed solution, stirring evenly, and then adding an organic metal catalyst to catalyze a reaction to obtain a prepolymer solution; (2) Adding a polyol chain extender, a polyol cross-linking agent, and a non-aqueous polyurethane defoaming agent to the prepolymer solution, stirring to react, and obtaining a polyurethane emulsion, and vacuum degassing and curing the polyurethane emulsion to obtain a degradable hydrophobic polyurethane.

3. The method for preparing the degradable hydrophobic polyurethane according to claim 2, characterized in that: In the step (1), the mass ratio of terminal hydroxyl polydimethylsiloxane, polycaprolactone and polylactic acid is 1:1.5-2:1.2-1.5; the amount of isophorone diisocyanate used is 20-50% of the total mass of terminal hydroxyl polydimethylsiloxane, polycaprolactone and polylactic acid.

4. The method for preparing the degradable hydrophobic polyurethane according to claim 2, characterized in that: In the step (1), the organic metal catalyst is dibutyltin dilaurate or stannous octoate, and the amount thereof is 0.1-1% of the mass of isophorone diisocyanate.

5. The method for preparing the degradable hydrophobic polyurethane according to claim 2, characterized in that: In the step (1), the catalytic reaction temperature is controlled at 50-90° C.; and the catalytic reaction time is controlled at 2-4 h.

6. The method for preparing the degradable hydrophobic polyurethane according to claim 2, characterized in that: In the step (2), the polyol chain extender is any one of 1,4-butanediol, propylene glycol, dimethylbenzene glycol, and triethanolamine, and its usage is 10-15% of the mass of isophorone diisocyanate; the polyol cross-linking agent is any one of trimethylolpropane, pentaerythritol, and trihydroxymethylethane; the non-aqueous polyurethane defoamer is any one of YRXP-02, YRXP-07, and YRXP-07B; the mass ratio of the polyol chain extender to the polyol cross-linking agent to the non-aqueous polyurethane defoamer is 1:0.4-0.6:0.03-0.

05.

7. A use of the degradable hydrophobic polyurethane as claimed in claim 1, characterized in that: The degradable hydrophobic polyurethane is applied to surface antifouling of marine materials.

Citation Information

Patent Citations

  • Preparation method of rapidly degradable polyurethane

    CN112409776A

  • Degradable material added with starch

    CN118184954A

  • Preparation method of polycaprolactone-based polyurethane containing poly-dimethylsiloxane

    CN101514242A

  • Degradable polyurethane, preparation method thereof, degradable artificial leather and application of degradable artificial leather

    CN109705308A

  • Preparation method and application of chain-extender-free type polysiloxane / polycaprolactone-based polyurethane elastomer

    CN110343232A

Cited By

  • Multi-performance synergistically reinforced composite epoxy resin material and preparation method thereof

    CN120865675A